Alignment of Knowledge Management and Performance Management System (Case Study: PT.X) - Atikah Aghdhi Pratiwi (LPPM of NAROTAMA UNIVERSITY, 2019)
Purpose: Improve company’s performance by capturing critical knowledges of employee in each Department. Design/methodology/approach: Knowledge audit is used to capture the knowledge database, and Analytical Hierarchy Process (AHP) is used to obtain critical knowledge. Findings: The results show that there are 30 points knowledges with 3 critical knowledges in the Department of Production. Research limitations/implications: The study focused only on E-Print product, especially for Department of Production. Practical implications: Knowledge is one of intangible assets in a company. Aligning knowledge with performance management system will support the company to achieve it’s goaals and the sustainability of the company. Paper type: This paper can be categorized as case study paper.